Measuring synergy within a Triple Helix innovation system using game theory: cases of some developed and emerging countries - Eustache Mêgnigbêto (Triple Helix, 2018)
Synergy within a Triple Helix innovation system has been measured in relevant literature using mutual information and transmission power, all based on Shannon's information theory. However, as a complex system, Triple Helix relationships may also be analysed with various techniques and tools from other disciplines among which game theory. Thus, the synergy may be measured with indicators like the core, the Shapley value and the nucleolus. The core measures the extent of the synergy, the Shapley value indicates an actor's strength to lead to and create synergy and the nucleolus determines an actor's strength to maintain synergy. The Triple Helix innovation systems of eight countries among which four developed-USA, UK, Germany and France-and four emerging-Russia, India, Brazil and China-were analysed based on their scientific output using game theory. It appears that the biggest Triple Helix science producer has more power to lead to and create synergy; government shows solidarity to maintain synergy within the innovation system. The level of synergy is higher in developing countries (led by France, 1.7-2%) than in emerging ones (led by Brazil, less than or equal to 1%), operating a division of selected countries according to their level of development. The study shows that state intervention in the economy influences the position of the core on a ternary diagram.
Keywords: 330; Triple Helix; Game theory; Innovation; Innovation system; Core; Shapley value; Nucleolus